2016
DOI: 10.1093/molbev/msw253
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Phylogenomics Resolves the Global Spread of Higher Termites, Ecosystem Engineers of the Tropics

Abstract: The higher termites (Termitidae) are keystone species and ecosystem engineers. They have exceptional biomass and play important roles in decomposition of dead plant matter, in soil manipulation, and as the primary food for many animals, especially in the tropics. Higher termites are most diverse in rainforests, with estimated origins in the late Eocene (∼54 Ma), postdating the breakup of Pangaea and Gondwana when most continents became separated. Since termites are poor fliers, their origin and spread across t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
173
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 93 publications
(205 citation statements)
references
References 37 publications
22
173
2
Order By: Relevance
“…Studies of unrelated taxa have suggested that this passage was used as a means of dispersal. For instance, Bourguignon et al () hypothesized that multiple clades of termites (Isoptera) used this bridge to disperse between the two continents. They argued that because these termite clades were fungus‐growers, geodispersal was more likely than LDD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of unrelated taxa have suggested that this passage was used as a means of dispersal. For instance, Bourguignon et al () hypothesized that multiple clades of termites (Isoptera) used this bridge to disperse between the two continents. They argued that because these termite clades were fungus‐growers, geodispersal was more likely than LDD.…”
Section: Discussionmentioning
confidence: 99%
“…Full mitochondrial genomes are a data‐rich and relatively accessible source of information, and promising results have been obtained for several insect families and orders (e.g. Haran et al ., ; Simon & Hadrys, ; Timmermans et al ., , ; Bourguignon et al ., , ). But there have been few mitophylogenomic studies with comprehensive taxon sampling for butterflies.…”
Section: Introductionmentioning
confidence: 99%
“…Samples forming a well‐supported cluster were named identically. Species names were carefully checked with available literature and correspond to those reported for Neotropical termites (Bourguignon et al., ; Cameron, Lo, Bourguignon, Svenson, & Evans, ; Casalla et al., ,b; Eaton et al., ; Inward et al., ; Roy et al., ). Voucher specimens of all species are held at the University of Freiburg, Germany, and will be deposited at the Natural History Museum of the Alexander von Humboldt Institute of Bogotá (MIAvH).…”
Section: Methodsmentioning
confidence: 99%